Evaluasi Dan Perbaikan Proses Bisnis Menggunakan Business Process Improvement (BPI) (Studi Kasus: Divisi PPID Komisi Pemilihan Umum Kota Malang) - Sheila Maulidia; Nanang Yudi Setiawan; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PPID department on KPU Malang city is a department that its function is to provide, serve, and publish public information. In the daily operation, some processes are still not optimal like data is not integrated, loss of data because of human error, and information that is not updated on timely manner because of poor management of information. Based on those mistakes, this research aim to evaluate current business process on PPID. Business process is modeled using Business Process Model and Notation (BPMN). After modeling the business process, the next step is to evaluate the business process and improving the business process. After the business processes are evaluated using Failure Mode and Effect Analysis (FMEA), the result is Risk Priority Number (RPN). Each of highest RPN from four business processes are solved using Business Process Improvement (BPI) method. The results of business process improvement are time improvement of 65.47% per process on penerimaan permohonan informasi publik process, time improvement of 99.47% per process on penyusunan laporan process, time improvement of 28.33% per process on pengesahan laporan process, and 97.46% per process on umpan balik laporan process.